C-arm CT Perfusion Study Using Angiography System - Tsuge, Yuichiro; Yamamoto, Kou; Sasanuma, Jinichi; Fujimoto, Michio; Moriya, Masao; Okamoto, Noriyoshi; Itokawa, Hiroshi (Journal of Neuroendovascular Therapy, 2019)
Objective: A newly developed application for cerebral C-arm computed tomography perfusion imaging (C-arm CTP) using an angiography system was investigated.Case Presentation: C-arm CTP protocol continuously collects X-ray projection images during 10 back and forth C-arm rotations. From the collected data, cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT), and time to peak (TTP) images and multiphase vascular images are reconstructed. C-arm CTP images acquired in patients with acute and chronic major artery occlusion are presented.Conclusion: C-arm CTP using an angiography system is capable of evaluating perfusion parameters in real time, similar to conventional evaluation using multi-detector row CT perfusion (MD-CTP), suggesting its usefulness for examination of ischemic stroke in the angiographic suite.